2016
DOI: 10.5539/ies.v9n5p247
|View full text |Cite
|
Sign up to set email alerts
|

Academic Quality Assurance Variables in Nigerian Universities: Exploring Lecturers’ Perception

Abstract: The level of job performance, international comparability and competitiveness of Nigerian university graduates are burning issues. Consequently, the academic quality of Nigerian universities has come under severe criticism. Since university lecturers are key players in quality assurance in universities, this study explored their perceptions of variables important to quality assurance in Nigerian universities. Five hundred lecturers from public universities in the South-South geopolitical zone responded to a 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This is because the problem-solving process in learning behavioral contract through cooperative learning promotes the acquisition of social skills as well as academic skills. (Obiekezie et al, 2016), on the other hand, emphasizes the importance of engaging and immersive learning activities in achieving learning objectives and promoting better learning. By taking into account the student's level of experience and learning goals, interesting learning activities can transform a dull learning module into a meaningful experience.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the problem-solving process in learning behavioral contract through cooperative learning promotes the acquisition of social skills as well as academic skills. (Obiekezie et al, 2016), on the other hand, emphasizes the importance of engaging and immersive learning activities in achieving learning objectives and promoting better learning. By taking into account the student's level of experience and learning goals, interesting learning activities can transform a dull learning module into a meaningful experience.…”
Section: Discussionmentioning
confidence: 99%
“…This is not the case in the labour market. Studies have shown the poor quality of Nigerian university graduates as result of overpopulated schools, poor quality of resources, among others [1,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%